2014
DOI: 10.1177/0959353514539653
|View full text |Cite
|
Sign up to set email alerts
|

The melancholy of murderous mothers: Depression and the medicalization of women’s anger

Abstract: Informed by recent feminist critiques of the notion of depression, we explored how a group of South African low-income mothers who have been diagnosed with depression subjectively describe and explain their psychological distress. Working within a feminist materialist-discursive framework, we focused both on the explicit content of what the women were saying and on the implicit or underlying discourses that informed their narratives. Our findings suggest that respondents often subjectively experienced their ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…Again these descriptions seem in line with studies conducted with adult women in this and other similar communities, where both the experiences of sadness and badness emerged as prominent properties in the experience of depression (Dukas, 2014;Kruger et al, 2014;Lourens & Kruger, 2013). Lourens and Kruger (2013) describe a range of feelings and behaviours reported by depressed women.…”
Section: Iii) Behaviours Of a Depressed Personsupporting
confidence: 87%
See 1 more Smart Citation
“…Again these descriptions seem in line with studies conducted with adult women in this and other similar communities, where both the experiences of sadness and badness emerged as prominent properties in the experience of depression (Dukas, 2014;Kruger et al, 2014;Lourens & Kruger, 2013). Lourens and Kruger (2013) describe a range of feelings and behaviours reported by depressed women.…”
Section: Iii) Behaviours Of a Depressed Personsupporting
confidence: 87%
“…It has been suggested that women's persistent anger may play a dominant role in their higher rates of depression (Simon & Lively, 2010). Kruger, Van Straaten, Taylor, Lourens and Dukas (2014), doing research in the same community as the participants, found that depressed mothers often experience severe anger, often expressing their anger through aggressive behaviour towards their children. While the anger and aggression reportedly caused these mothers great distress , it is highly likely that some of the girls in our study have experienced the rage of a depressed mother.…”
Section: Participant 9: "…Then I Get Angry and Scream…or If I Don't Fmentioning
confidence: 97%
“…As feminist theorists have argued, motherhood is not necessarily devoid of conflicting feelings of resentment, hostility or destructive impulses (Kruger, van Straaten, Taylor, Lourens, & Dukas, 2014; Murray & Finn, 2012). Globally, rates of antenatal depression and anxiety range between 15 and 40 per cent (Howard et al., 2014).…”
mentioning
confidence: 99%
“…Feminist psychologists have critiqued the effects of medicalisation, for example raising concerns about the medicalisation of women's anger (Kruger et al, 2014), women's hormonal changes (Liebert, 2010), women's misery (Ussher, 2010) and trans youth seeking gender-affirming healthcare (Roen, 2011(Roen, , 2018. The Feminism & Psychology special issue "DSM-5 and Beyond" (Marecek & Gavey, 2013) addresses criticisms of the biomedical model of mental health.…”
Section: Bringing Decolonisation Into Dialogue With Demedicalisationmentioning
confidence: 99%